The Affordable Care Act's Medicaid Expansion and Impact Along the Cancer-Care Continuum: A Systematic Review - Moss, Haley A; Wu, Jenny; Kaplan, Samantha J; Zafar, S Yousuf (JNCI : Journal of the National Cancer Institute, 2020)
Health reform and the merits of Medicaid expansion remain at the top of the legislative agenda, with growing evidence suggesting an impact on cancer care and outcomes. A systematic review was undertaken to assess the association between Medicaid expansion and the goals of the Patient Protection and Affordable Care Act in the context of cancer care. The purpose of this article is to summarize the currently published literature and to determine the effects of Medicaid expansion on outcomes during points along the cancer care continuum. A systematic search for relevant studies was performed in the PubMed/MEDLINE, EMBASE, Scopus, and Cochrane databases. Three independent observers used an abstraction form to code outcomes and perform a quality and risk of bias assessment using predefined criteria. A total of 48 studies were identified. The most common outcomes assessed were the impact of Medicaid expansion on insurance coverage (23.4% of studies), followed by evaluation of racial and/or socioeconomic disparities (17.4%) and access to screening (14.5%). Medicaid expansion was associated with increases in coverage for cancer patients and survivors as well as reduced racial- and income-related disparities. Medicaid expansion has led to improved access to insurance coverage among cancer patients and survivors, particularly among low-income and minority populations. This review highlights important gaps in the existing oncology literature, including a lack of studies evaluating changes in treatment and access to end-of-life care following implementation of expansion.